Combination of morphological and multiparametric MR neurography enhances carpal tunnel syndrome diagnosis and evaluation - Youzhi Wang; Wenjun Wu; Jiamin Kang; Yu Su; Tingting Liu; Jie Zhao; Dingxi Liu; Xiangchuang Kong; Yuxiong Weng; Chuansheng Zheng; Chungao Li; Lixia Wang (Scientific Reports)
Abstract This study aimed to investigate the diagnostic and evaluative significance of combining median nerve (MN) morphological measurements with diffusion tensor imaging (DTI) and T2 mapping metrics for carpal tunnel syndrome (CTS). Morphological and multiparametric magnetic resonance neurography (MRN), along with clinical evaluation, were conducted on 33 CTS patients and 32 healthy controls. The MRN metrics included fractional anisotropy (FA), apparent diffusion coefficient (ADC), axial diffusivity (AD), radial diffusivity (RD), T2 value, cross-sectional area (CSA) and MN flattening ratio (MNFR) at both the pisiform bone and hamate bone levels. Differences in MRN metrics between the above two levels (Delta FA, Delta ADC, Delta AD, Delta RD and Delta T2) were calculated. T-tests, multivariable regression, and receiver operating characteristic (ROC) curve analyses were used to compare and classify patients with CTS and controls. The correlations between MRN metrics and clinical characteristics were analyzed. Comparisons were also made between MRN metrics in patients with and without significant symptom improvement after treatment. FA, AD, T2 value, and CSA at the pisiform bone level were identified as independent predictors of CTS. The combination of these metrics improved diagnostic performance (AUC 0.922, sensitivity 84.85% and specificity 90.62%). Delta ADC, Delta AD, and Delta T2 correlated with function Boston scores. The T2 value at hamate bone level, along with Delta AD and FA, correlated with visual analogue score (VAS). CSA and Delta T2 had higher AUCs for classifying patients with and without significant symptom improvement after treatment. These findings suggest that combining MN morphological and multiparametric MRN metrics can enhance the diagnostic performance of CTS and has the potential to provide an objective and quantitative basis for further study of the degree of entrapment and prognosis.